Tetracycline hydrochloride-stressed succession in microbial communities during aerobic composting: Insights into bacterial and fungal structures. (February 2022) - Cui, Hu; Ou, Yang; Wang, Lixia; Yan, Baixing; Bao, Meiwen
Abstract: Available information that whether antibiotics affect the succession in microbial communities during aerobic composting remains limited. Thus, this work investigated the dynamic changes in bacterial and fungal structures during aerobic composting amended with tetracycline hydrochloride (TCH: 0, 50, 150 and 300 mg kg −1 ). Composting phases significantly affected bacterial and fungal communities, but only fungi strongly responded to antibiotics, while bacteria did not. Firmicutes, Proteobacteria, Bacteroidota and Actinobacteriota were primary bacterial phylum. Neocallimastigomycota was dominant fungal phylum at temperature-heating phase, then Basidiomycota and Ascomycota became main fungal phylum at thermophilic and temperature-colling phases. Low TCH concentration promoted Chytridiomycota growth, while high TCH concentration inhibited mostly fungal activity in TCH-amended composting. Nitrogen species were critical factors controlling the succession in bacterial and fungal communities during composting process. These results cast a new light on understanding about microbial function during aerobic composting. Graphical abstract: Image 1 Highlights: TCH showed insignificant influence on temperature at the thermophilic phase. Thermophilic phase reduced microbial richness and diversity. TCH affected the fungal succession during composting process. Low TCH concentration promoted Chytridiomycota growth. TCH affected microbial succession through controlling nitrogen species.